2000
DOI: 10.1042/bj3460659
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AMP-activated protein kinase γ-subunit isoforms and their role in AMP binding

Abstract: The AMP-activated protein kinase (AMPK) cascade plays an important role in the regulation of energy homeostasis within the cell. AMPK is a heterotrimer composed of a catalytic subunit (alpha) and two regulatory subunits (beta and gamma). We have isolated and characterized two isoforms of the gamma subunit, termed gamma2 and gamma3. Both gamma2 (569 amino acids) and gamma3 (492 amino acids) have a long N-terminal domain which is not present in the previously characterized isoform, gamma1. As with gamma1, mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
391
4
11

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 525 publications
(444 citation statements)
references
References 40 publications
28
391
4
11
Order By: Relevance
“…The a2 AMPK activity was similar to that previously reported 8 but represented only 5% of the total activity of AMPK, in agreement with the repartition of a isoforms of AMPK reported for the whole brain. 24 Immunoblots with specific antibodies confirmed that the a1 isoform of AMPK was predominant in the whole hypothalamus. The liver, which contains about equal amounts of both AMPK isoforms, was taken as a control (Figure 1d).…”
Section: Resultsmentioning
confidence: 84%
“…The a2 AMPK activity was similar to that previously reported 8 but represented only 5% of the total activity of AMPK, in agreement with the repartition of a isoforms of AMPK reported for the whole brain. 24 Immunoblots with specific antibodies confirmed that the a1 isoform of AMPK was predominant in the whole hypothalamus. The liver, which contains about equal amounts of both AMPK isoforms, was taken as a control (Figure 1d).…”
Section: Resultsmentioning
confidence: 84%
“…Previously it has been demonstrated that in the rodent liver, the AMPKα1-and AMPKα2-containing complexes account for about half of total AMPK activity each [23]. In human liver, and in the human hepatocyte cell line HepG2, the abundance of the two isoforms of the catalytic subunit has not been previously described.…”
Section: Both Ampkα1 and Ampkα2 Isoforms Are Produced In Hepg2 Cellsmentioning
confidence: 99%
“…5 This increase in AMP levels leads to allosteric activation of AMPK through AMP binding to the g-subunit. 10 Recent data suggest that AMP binding also induces a conformational change in the kinase domain leading to protection of Thr172 from dephosphorylation. Thus, increases in AMP levels play dual roles in activation of AMPK.…”
Section: Expression Of Ampk In Skeletal Musclementioning
confidence: 99%